Evidence of the impact of Scholarship of Teaching and Learning purposes - Trigwell, Keith (Teaching and Learning Inquiry, 2013)
This paper identifies a need for empirical studies to validate the purposes of the Scholarship of Teaching and Learning (SoTL) and reports the results of an investigation into one purpose based on one definition. The SoTL movement needs to be seen to be scholarly and to be engaging in evidence-based practice. More evidence is needed on whether SoTL is achieving its purposes and whether those purposes are worthwhile. The study was designed to address this issue by assessing whether one acknowledged purpose of SoTL (to enhance students’ experience of learning) is being achieved. Questionnaires on SoTL and approaches to teaching were used to capture the experiences of 56 faculty. It is concluded that when teaching is seen as scholarly and inquiring and when it is made public and peer reviewed, there is a stronger likelihood that the improving student learning purposes of SoTL are being achieved.